OS 14-07 PULSE WAVE VELOCITY COMPARED WITH MEAN ARTERIAL PRESSURE AND PULSE PRESSURE PROGNOSTIC IN THE POPULATION OF GAOYOU COUNTY, CHINA. (September 2016) - Lu, Yichao; Zhang, Haifeng; Zhou, Fang; Li, Shan-Shan; Wei, Fang-Fei; Yao, Wen-Ming; Gong, Lei; Zhou, Yan-Li; Kong, Xiang-Qing
Abstract : Objective: To evaluate the predictive value for cardiovascular disease incidence (CVD) of brachial-ankle pulse wave velocity (baPWV) based on a general Chinese population. Design and Method: The study group included 4251 participants with an average age of 52.1 ± 12.1 years and a mean baPWV of 14.8 ± 3.3 m/s. Cox regression was used to investigate the prognostic value of baPWV and forced the appropriate interaction term into the regression models to test the absolute risk associated with baPWV at different levels of mean arterial pressure. Results: Over a median follow-up of 4.4 years, the incidence of cardiovascular mortality, stroke and composite cardiovascular endpoints amounted to 21, 48 and 74. We adjusted for sex, age, body mass index, mean arterial pressure, waist-to-hip ratio, total cholesterol, current smoking, alcohol intake, blood glucose and use of antihypertensive drugs. With these adjustments, for each 1-SD increment in baPWV (3.23 m/s), the hazard ratios for an all-cause mortality, cardiovascular mortality, stroke or composite cardiovascular outcomes were 1.41(1.13–1.75), 1.68 (95% CI:1.20–2.35), 1.51 (95% CI:1.27–1.80), 1.57 (95% CI: 1.28–1.93), respectively. At any given level of mean arterial pressure (MAP), a higher baPWV was associated with a higher death rate. The area under curve (AUC) of baPWV was larger than pulse pressure in predicting composite cardiovascular events (Z = 2.45, P = 0.014). Conclusions: In conclusion, baPWV predicted a composite of cardiovascular outcomes above and beyond pulse pressure in a general Chinese population.